Remittances as moral battlegrounds: navigating the qualitative meanings of money, power, and intimacy in translocal Chinese families - Wang, Zhenwei (Journal of ethnic and migration studies, 2025)
Aiming to illuminate the role of remittances in shaping intergenerational and gender relations, this paper argues that in translocal Chinese families, remittances are far more than mere economic transfers; they are deeply imbued with moral and emotional significance, functioning as dynamic ‘battlegrounds’. Drawing on Mauss's ‘gift’ and Zelizer's concept of ‘multiple monies’, this study examines how the qualitative meaning of money - infused with affective obligations and social expectations - is actively encoded through situated moral vocabularies, often surpassing its quantitative value in defining family ties and reshaping authority. The ethnographic fieldwork between 2020 and 2024 reveals that both classic (migrant-to-origin) and reverse (origin-to-migrant) remittances become crucial sites for intense, often unspoken, struggles over autonomy, authority, and emotional intimacy. The findings demonstrate a persistent intergenerational paradox: while migrants' financial contributions provide crucial material support and allow them to assert a new provider identity, they often clash with older generations’ desires for traditional forms of care, control, and physical presence. This study underscores the deeply contested nature of remittance in reaffirming, negotiating and paradoxically challenging intersecting intergenerational and gender hierarchies. It contributes to migration and kinship scholarship by illuminating how translocal mobility transforms moral economies and familial subjectivities.